2011
DOI: 10.1007/s10103-011-1011-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser irradiation, cyclooxygenase-2 (COX-2) expression and necrosis of random skin flaps in rats

Abstract: Skin flaps are still a matter of concern among surgeons, as failures can occur leading to flap necrosis. However, low-level laser irradiation has been reported as an effective tool to improve the viability of ischemic flaps, yet its mechanisms of action remain unclear. We investigated the effect of low-level laser irradiation on the viability of random skin flaps in rats and determined COX-2 expression in the flap pedicle. The study animals comprised 24 EPM-1 Wistar rats which were randomly allocated into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Several recent reports have suggested that low level red/near infrared light irradiation is an effective alternative treatment that reduces inflammation caused by periodontal disease . Many physiological studies have reported that low‐level laser treatment (LLLT) and light‐emitting diode treatment (LEDT) can reduce pain and inflammation and accelerate wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have suggested that low level red/near infrared light irradiation is an effective alternative treatment that reduces inflammation caused by periodontal disease . Many physiological studies have reported that low‐level laser treatment (LLLT) and light‐emitting diode treatment (LEDT) can reduce pain and inflammation and accelerate wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have focused on enhancing flap viability to avoid potential necrosis of the flaps [123]. Various pharmacological and surgical delay procedures may be used for enhancement of skin flap viability [3].…”
mentioning
confidence: 99%
“…Random skin flaps have been widely used for loss of skin and subcutaneous tissues for thousands of years [ 1 ]. Unlike the axial pattern flap, the blood supply of a random pattern flap is based on small unnamed vessels.…”
mentioning
confidence: 99%
See 1 more Smart Citation